2021
DOI: 10.1111/1365-2664.13895
|View full text |Cite
|
Sign up to set email alerts
|

The impact of logging on vertical canopy structure across a gradient of tropical forest degradation intensity in Borneo

Abstract: 1. Forest degradation through logging is pervasive throughout the world's tropical forests, leading to changes in the three-dimensional canopy structure that have profound consequences for wildlife, microclimate and ecosystem functioning.Quantifying these structural changes is fundamental to understanding the impact of degradation, but is challenging in dense, structurally complex forest canopies.2. We exploited discrete-return airborne LiDAR surveys across a gradient of logging intensity in Sabah, Malaysian B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 76 publications
2
29
1
Order By: Relevance
“…A myriad of other factors that we were unable to quantify in our analysis also contribute to losses in forest integrity across tropical moist forests 37 . These include alteration of microclimates, proliferation of lianas, and the cascading ecological effects resulting from selective logging, road edges, and reduced populations of large-bodied vertebrates 38,39 . The complexities of monitoring forest degradation using remote sensing not withstanding 40 , our finding that short term tree cover loss is reduced relative to non-protected areas and comparably with PAs is encouraging, since 45% of short-term degradation leads to deforestation, particularly in Southeast Africa and Southeast Asia 24 .…”
Section: Deforestation and Degradation On Indigenous Landsmentioning
confidence: 99%
“…A myriad of other factors that we were unable to quantify in our analysis also contribute to losses in forest integrity across tropical moist forests 37 . These include alteration of microclimates, proliferation of lianas, and the cascading ecological effects resulting from selective logging, road edges, and reduced populations of large-bodied vertebrates 38,39 . The complexities of monitoring forest degradation using remote sensing not withstanding 40 , our finding that short term tree cover loss is reduced relative to non-protected areas and comparably with PAs is encouraging, since 45% of short-term degradation leads to deforestation, particularly in Southeast Africa and Southeast Asia 24 .…”
Section: Deforestation and Degradation On Indigenous Landsmentioning
confidence: 99%
“…For instance, total gap fraction and gap size frequency distributions have been shown to closely reflect tree mortality rates and reliably detect the effects of selective logging in tropical forests (Dalagnol et al, 2021; Kent et al, 2015; Reis et al, 2021; Wedeux & Coomes, 2015). Beyond gaps, the impacts of logging and habitat fragmentation can also be seen in dramatic changes in the vertical distribution and density of foliage and woody biomass captured by LiDAR (Milodowski et al, 2021), and the spatial and temporal extent of structural change due to habitat fragmentation. A combination of airborne LiDAR and hyperspectral imaging in Borneo has shown that above‐ground carbon stocks are >20% lower in the first 100 m from a forest edge, and that these changes are linked to declines in canopy height and shifts in foliar traits related to light capture, growth and longevity such as leaf mass per area and phosphorus content (Ordway & Asner, 2020).…”
Section: Sensing Drivers Of Canopy Structure and Complexity From Loca...mentioning
confidence: 99%
“…Long-term experiments, such as the Stability of Altered Forest Ecosystem (SAFE) project (Ewers et al, 2011), have substantially contributed to our understanding of how deforestation, forest fragmentation, and logging modify the functioning of tropical forests. Numerous studies have been conducted to understand the effects of logging on forest structure (Milodowski et al, 2021;Pfeifer et al, 2015), primary productivity (Riutta et al, 2018), biodiversity (Struebig et al, 2013), and biomass (Jucker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Approaches aimed at collecting three-dimensional (3D) information such as Synthetic Aperture Radar (SAR) (Treuhaft and Siqueira, 2000), and Light Detection and Ranging (LiDAR) can provide a more detailed description of the forest structure (Dubayah and Drake, 2000). Airborne Laser Scanning (ALS) collects 3D data from above the canopy and has been widely used to quantify forest biomass and carbon (Asner et al, 2018;Coomes et al, 2017;Ellis et al, 2016;Jucker et al, 2018), and to identify disturbances caused by selective logging (Andersen et al, 2014;Ellis et al, 2016;Milodowski et al, 2021). However, despite considerable progress offered by ALS system in assessing forest disturbance (Jucker et al, 2018;Kent et al, 2015) the occlusion in dense vegetation using ALS data makes it difficult to detect fine structural details of the forest understory.…”
Section: Introductionmentioning
confidence: 99%